Mode of Slope Failure of Moderately to Completely Weathered Metasedimentary Rock at Bukit Panji, Chendering, Kuala Terengganu (Journal of Tropical Resources and Sustainable Science (JTRSS), 2015)
Geology of Bukit Panji, Chendering, Kuala Teregganu consists of interbededmetasedimentary rocks (slate, phyllite and schists with minor quartzite) which have experience regional metamorphism. The age of this rock is Carboniferous. A development project which under construction in Bukit Panji, Kuala Terengganu has enabled a landslide assessment to observe the modes of failure in moderately to completely weathered metasedimentary rock. Development on hillsides caused many slope had to be cut to provide space for the infrastructure construction. From assessment analysis, a total of 21 cases of landslide failure occurred involving 17 cut slopes, and 4 cut-fill slopes. The most common type of failures is gully failures, with 9 cases represent 43% of all the observed slope failure. This was followed by 6 wedge failures, two planar and rock fall failures and one shallow sliding and toppling respectively. Cut slope failure involving moderate weathered rock mass (grade III) to the residual soil (grade VI). Relict structure was identified as the main factors controlling the failure, as well as water, natural slope-forming materials and the use of appropriate slope stabilization.
Keywords: Metasedimentary rock; landslide assessment; weathering; mode of failure